DETERMINANTS OF JOB PERFORMANCE AMONG MUSLIM ACCOUNTANTS IN INDONESIAN HOSPITALS: A PROPOSED CONCEPTUAL FRAMEWORK - Hadi, Syukry; Yasin, Nurul Hafizah; Mohamad, Siti Rohana (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Hospitals operate in increasingly complex and regulated environments, where effective financial management is essential for organisational sustainability. Despite their strategic role in budgeting, financial reporting, compliance, and resource allocation, hospital accountants remain underexplored in performance-related research, particularly within Islamic and healthcare contexts. This study proposes a conceptual framework to explain the determinants of job performance among Muslim accountants in Indonesian hospitals by integrating Herzberg’s Motivation–Hygiene Theory with Islamic Work Ethics (IWE). Drawing on prior literature in healthcare management, accounting, and organisational behaviour, the framework examines how internal factors (achievement, recognition, advancement, and growth) and external factors (organisational policies, supervisory relationships, peer relationships, and job security) influence job performance through the mediating role of IWE. The proposed model argues that internal motivational factors align closely with Islamic ethical values, thereby strengthening intrinsic commitment and ethical behaviour, while favourable external conditions create an ethical climate that facilitates the internalisation of these values. By positioning IWE as a central mediating mechanism, this study extends Herzberg’s theory by embedding a culturally grounded ethical dimension relevant to Muslim professionals. The framework contributes to healthcare accounting literature by offering a more comprehensive understanding of performance determinants and provides practical insights for hospital administrators to enhance accountant performance, reinforce ethical financial practices, and support the long-term sustainability of healthcare organisations in Indonesia.